Search for Higgs boson decays to beyond-the-Standard-Model light bosons in four-lepton events with the ATLAS detector at $\sqrt{s}=13$ TeV - ATLAS collaboration (2900 authors); Aguilar-Saavedra, Juan Antonio; Amor Dos Santos, Susana Patricia; Anjos, Nuno; Araque, Juan Pedro; Castro, Nuno Filipe; Conde Mui\~no, Patricia; Da Cunha Sargedas De Sousa, Mario Jose; Fiolhais, Miguel; Galhardo, Bruno; Gomes, Agostinho; Gon\c calo, Ricardo; et al. (My University, 2018)
A search is conducted for a new beyond-the-Standard-Model boson using events where a Higgs boson with mass 125 GeV decays to four leptons ($\ell =$ $e$ or $\mu$). This decay is presumed to occur via an intermediate state which contains one or two on-shell, promptly decaying bosons: $H\rightarrow ZX/XX \rightarrow 4\ell$, where $X$ is a new vector boson $Z_d$ or pseudoscalar $a$ with mass between 1 and 60 GeV. The search uses $pp$ collision data collected with the ATLAS detector at the LHC with an integrated luminosity of 36.1 fb$^{-1}$ at a centre-of-mass energy $\sqrt{s}=13$ TeV. No significant excess of events above Standard Model background predictions is observed; therefore, upper limits at 95% confidence level are set on model-independent fiducial cross-sections, and on the Higgs boson decay branching ratios to vector and pseudoscalar bosons in two benchmark models.